Pengaruh Organizational Justice Dan Gaya Kepemimpinan Transformational Terhadap Employee Engagement Dengan Kepuasan Kerja Sebagai Variabel Intervening di Hotel Axana Kota Padang - Siti Permata Pricilla (Departemen Pariwisata Universitas Negeri Padang, 2024)
This research is driven by a decline in work discipline among employees at Axana Padang Hotel, where turnover and tardiness data have been varied and tend to increase from 2019 to 2022. This decline in discipline suggests a drop in employee engagement. Thus, this study aims to explore how employees' perceptions of organizational justice, transformational leadership style, and job satisfaction as an intervening variable influence this engagement. The study employs a quantitative approach and focuses on the employees of Axana Padang Hotel in West Sumatra. The population of this study consists of 139 individuals, with a saturated sampling method, meaning all 139 individuals were included as the sample. The data were gathered through the use of questionnaires and the analysis was conducted using Descriptive Statistical Analysis and Partial Least Square (PLS). The results revealed that organizational justice significantly and positively impacts job satisfaction, transformational leadership style has a significant and positive effect on job satisfaction, and job satisfaction in turn has a significant and positive effect on employee engagement. In conclusion, higher levels of organizational justice and transformational leadership, mediated by job satisfaction, lead to improved employee engagement with the company.